2015
DOI: 10.1159/000430389
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Promotes Pancreatic Cancer Growth by Inhibiting Tristetraprolin

Abstract: Background/Aims: The microRNA (miR) 29 family has been studied extensively for its involvement in several diseases, and aberrant expression of its members is associated with tumorigenesis and cancer progression. Here, we examined the role of miR-29a in pancreatic cancer and the involvement of tristetraprolin (TTP). Methods: We monitored miR-29a and TTP expression in pancreatic cancer by qRT-PCR and western blotting. The effect of miR-29a on pancreatic cancer was determined through MTT assay and migration assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…However, the function and mechanism of these deregulated miRNAs in various cancers including PC remain undefined. To date, various miRNAs (including miR-21, miR-34a, miR-155 , and miR-29a ) has been shown to be associated with tumor progression and overall survival in patients with PC [10, 25]. Most miRNAs are known to regulate target mRNAs by binding to the 3′ UTR of target genes in a posttranscriptional manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the function and mechanism of these deregulated miRNAs in various cancers including PC remain undefined. To date, various miRNAs (including miR-21, miR-34a, miR-155 , and miR-29a ) has been shown to be associated with tumor progression and overall survival in patients with PC [10, 25]. Most miRNAs are known to regulate target mRNAs by binding to the 3′ UTR of target genes in a posttranscriptional manner.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that deregulated expression of series miRNAs correlates with PC development [10]. Through the online tools and luciferase assay, we found that microRNA-195 ( miR-195 ) directly targets DCLK1 .…”
Section: Introductionmentioning
confidence: 98%
“…Recently, many studies have shown that miRNAs are involved in various diseases, including cancers [10-17]. Using high-throughput RNA sequencing and bioinformatics, an increasing number of functional miRNAs have been discovered, which might participate in tumor development and could provide novel targets for pancreatic cancer therapies [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies indicate that miRNAs have important functions in tumor occurrence and development [10, 11]. Recent studies have revealed that miRNAs are associated with the risk of different cancers, such as lung cancer [12], colorectal cancer [13], bladder cancer [14], breast cancer [15], and pancreatic cancer [16, 17]. All of these researches have provided strong evidence that miRNAs play a key role during tumorigenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of molecules have been implicated in the development and progression of pancreatic cancer, such as stat3 [23], FoxM1 [24], IL-1β and miR-29a [25]. Caveolin-1 (Cav-1), the major structural protein of plasma membrane invaginations [26], is a key signal transducer in various human cancers [27-29].…”
Section: Introductionmentioning
confidence: 99%